P0891META-ANALYSIS OF NUTRITIONAL VITAMIN D FOR THE TREATMENT OF SECONDARY HYPERPARATHYROIDISM IN PATIENTS WITH NON-DIALYSIS CHRONIC KIDNEY DISEASE. (6th June 2020) - Gunnarsson, Joel; Lauppe, Rosa; Kaiser, Edelgard; Soro, Marco; Csomor, Philipp
Abstract: Background and Aims: Chronic kidney disease (CKD) is commonly associated with mineral and bone disorder (CKD-MBD). Secondary hyperparathyroidism (SHPT) is a critical component of CKD-MBD characterized by excessive PTH secretion and parathyroid hyperplasia. SHPT develops in CKD because of disturbances in CKD-MBD parameters such as increases in serum phosphate and fibroblast growth factor 23, and reductions in 25-hydroxyvitamin D (25(OH)D), 1, 25-dihydroxyvitamin D (1, 25(OH)2D) and serum calcium. Low vitamin D levels play a critical role in the development and progression of SHPT. Nutritional vitamin D (NVD) supplements are being frequently used to address SHPT, especially in early CKD. The objective of this meta-analysis (MA) was to evaluate the effectiveness of the NVDs cholecalciferol and ergocalciferol in reducing PTH and increasing 25(OH)D in patients with non-dialysis CKD (ND-CKD). Method: A systematic literature search was performed in PubMed to identify relevant randomized control trials (RCTs) to be included in the MA. All analyses were performed using both random and fixed effects models with inverted-variance weighting. Comparisons were made between the effects of NVDs relative to placebo-treated or untreated patients and between the baseline and end-of-study values of the patients treated with the NVDs, i.e. the effects in treated patients only. Results: A total of 14 RCTs comprising 974 patients were included in the analyses. Overall reductions in PTH were small when compared to baseline (reduction of 10.95 pg/ml, 95 % confidence interval (CI): -15.99 to -5.91 pg/ml), while reductions in PTH were approximately three times larger when compared to placebo-treated or untreated patient groups (reduction of 34.35 pg/ml, 95 % CI:-47.47 to -21.24 pg/ml). This indicated a limited potential to actively lower PTH with NVDs as the relative effect on PTH when compared to placebo-treated or untreated patient groups was driven to a large degree by increases in PTH in the comparator arms. Treatment with NVDs tended to increase levels of 25(OH)D both when compared to placebo-treated or untreated patients (increase of 26.54 ng/ml, 95 % CI: 24.62 to 28.46 ng/ml) and when only the changes in treated patients were considered (increase of 21.49 ng/ml, 95 % CI: 20.54 to 22.44 ng/ml). However, large variations in effect sizes on levels of 25(OH)D were observed, making judgements about the size of any true treatment effect difficult. Average levels of 25(OH)D in treated patients at the end of the study period were >30 ng/ml in all but two RCTs and >50 ng/ml in only five of the included RCTs. No clear relationship was observed between study length (range: 4 to 144 weeks) or doses administered (range: 14 000 to 75 000 UI weekly average) and effects on 25(OH)D or PTH. Conclusion: Our results suggest that treatment with NVDs is not efficacious to reliably and consistently lower PTH in ND-CKD patients with SHPT. Although treatment with NVDs can potentially be used to correct vitamin D insufficiency, our results suggest that the potential of NVD treatment to raise 25(OH)D levels to >50 ng/ml, a level needed to reduce PTH, is limited.